2021
DOI: 10.1038/s41467-021-23856-9
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the one carbon folate cycle as a shared metabolic signature of longevity

Abstract: The metabolome represents a complex network of biological events that reflects the physiologic state of the organism in health and disease. Additionally, specific metabolites and metabolic signaling pathways have been shown to modulate animal ageing, but whether there are convergent mechanisms uniting these processes remains elusive. Here, we used high resolution mass spectrometry to obtain the metabolomic profiles of canonical longevity pathways in C. elegans to identify metabolites regulating life span. By l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 84 publications
4
25
0
4
Order By: Relevance
“…The impaired one-carbon metabolism and lower folate levels tightly correlated with elevated tau phosphorylation levels in neurodegenerative diseases and disturbed neuronal homeostasis [31]. However, recent research on the genetic and supplementation-manipulated C. elegans indicated that specific folate and one carbon metabolism reduction could be beneficial for longevity and proteoprotection [32]. These disparate observations probably reflect multi-layering of FFE effects on LPS-induced BV-2 cells since it could effectively decrease pro-inflammatory factor expression and downregulate folate metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired one-carbon metabolism and lower folate levels tightly correlated with elevated tau phosphorylation levels in neurodegenerative diseases and disturbed neuronal homeostasis [31]. However, recent research on the genetic and supplementation-manipulated C. elegans indicated that specific folate and one carbon metabolism reduction could be beneficial for longevity and proteoprotection [32]. These disparate observations probably reflect multi-layering of FFE effects on LPS-induced BV-2 cells since it could effectively decrease pro-inflammatory factor expression and downregulate folate metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transcriptional activation of glycine metabolism and folate-dependent OCM is a prominent trait of longevity shared between seemingly different longevity paradigms [ 65 ]. Recently, it was reported that folate intermediates undergo extensive quantitative changes that are often common among long-lived nematode mutants [ 63 ]. Folate, THF, and 5,10-methylene-THF are increased while 5-methyl-THF, 10-formyl-THF, and 5,10 methenyl-THF are robustly and reproducibly decreased.…”
Section: One-carbon Metabolism In Agingmentioning
confidence: 99%
“…Similar data were obtained when the DHFR enzyme was genetically suppressed in nematodes, also leading to lifespan extension. Notably, supplementation with 5-methyl-THF reversed longevity of long-lived mutants, of reduced insulin signaling (rIIS), inherently caloric restricted, and mitochondrial mutants, while folic acid supplementation did not alter lifespan of wt nematodes [ 63 ]. Conclusively, increasing reports suggest that altered OCM may be a shared metabolic trait of longevity.…”
Section: One-carbon Metabolism In Agingmentioning
confidence: 99%
“…Adam Antebi, Max Planck Institute for Biology of Ageing, Germany, presented their latest study in which they used metabolic profiling of longlived C. elegans strains and identified the folate/ methionine cycle as a convergence point of aging pathways. This elucidates how single genes or metabolites can regulate lifespan through multiple pathways [16].…”
Section: Longevity Pathwaysmentioning
confidence: 99%